Students Needs in Learning English in the Medical Faculty of Muhammadiyah University at Malang - Langgeng Budianto (Universitas Negeri Malang, 2016)
The English course offered in medical faculty of Muhammadiyah University of Malang (MUM) was not based on the needs of the students. This may cause lack of students motivation and participation in the course. The purpose of this study was to identify the most fundamental needs of the medical students in learning English. Identification of students needs in English course was conducted to 36 students of medical faculty by using questionnaire. The results indicated that 18 respondents (50%) stated that they needed English for developing career, finishing study and widening international relationship. Eighteen respondents (50%) stated that they needed speaking and reading skills for their future career. Further, twenty-seven (75%) respondents explained that they needed the materials relevant to their study.